Systematic ichnology of the Middle Ordovician Trenton Group, St Lawrence Lowland, eastern Canada - Fillion, D.; Pickerill, R. (Atlantic Geology, 1984)
Carbonate sediments of the upper Middle Ordovician Trenton Croup between Montreal and Quebec City in the St. Lawrence Lowland, eastern Canada, contain a diverse and abundant trace fossil assemblage consisting of Arenlcolltes sp., ?Calycraterion sp., Chondrites spp., Circullchnls montanus, Clem at is-chnla sp., ?Conoatlchniu sp., Cruzlana problematical Cruz tana sp., cf. Dlpllchnltes sp., Furculosus car-pathlcus, Helmlnthopsis hieroglyphlca, Helminthopsis sp., Oichnus parabololdes, Palaeophycus tubularis, Palaeophycus sp., ?P!ag1ogmus sp., Planolltes beverleyensls, P. montanus, Planolltes sp., ?Rhlzocorallium cf. R. Irregulare, ?Rossella sp., Scalar 1 tuba mlsourlensls, Scolicla sp., Skolithos linearis, Skolithos sp„ Teichichnus rectus, Teichichnus sp., Trichichnus sp., Trypanltes weisei, Vermlforichnus clarkel and Zoo-phycos sp. as well as informally diagnosed loop, oblique and pronged burrows and bryozoan borings. Of these forms, only Chondrites spp., Palaeophycus tubularis, Palaeophycus sp., Planolltes spp., Teichichnus spp. and Trypanltes weisei are abundant; the remainder are rare to only moderately common. Nevertheless, in this paper we describe all the trace fossils in detail and in doing so attempt to resolve several current and controversial problems of nomenclature regarding certain ichnogenera. Sediments of the Trenton Group were deposited Initially In lagoons followed in turn by offshore "bar", shallow and, finally, deeper offshore shelf environments. The trace fossils do not exhibit significant variation with respect to these broad depositlonal regimes and, Instead, each environment Is characterized by assemblages typical of the Cruzlana ichnofacies as recognized in clastic sequences. The major factor primarily limiting the spatial and temporal trace fossil distribution was substrate and its primary characteristics, in turn a reflectance of food availability and environmental energy levels.